2017
DOI: 10.1002/2017gl072894
|View full text |Cite
|
Sign up to set email alerts
|

Major dust storms and westward traveling waves on Mars

Abstract: Westward traveling waves are observed during major dust storm periods in northern fall and winter. The close correlation in timing makes westward traveling wave one of the signature responses of the Martian atmosphere to major dust storms. Westward traveling waves are dominated by zonal wave number m = 1 in the middle atmosphere and are typically characterized by long wave period. They are associated with significant temperature perturbations near the edge of the north polar vortex. Their wind signals extend t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 29 publications
1
13
0
Order By: Relevance
“…It should be noted that despite the narrowness of the peaks of the 8 < P ≤ 60 sol eddies in Fig. 2a&c, these results are consistent with Wang (2017) because the vertical integration in the KE calculation and the non-linear relationship between KE and the eddy winds sharpens the changes in KE versus the signatures in temperature observations. Murphy et al (1995) also found a slowly propagating westward wave in their global dust storm simulation and suggested that the westward wave signals polar warming.…”
Section: Evolution Of Globally Averaged Eddy Kinetic Energysupporting
confidence: 78%
See 1 more Smart Citation
“…It should be noted that despite the narrowness of the peaks of the 8 < P ≤ 60 sol eddies in Fig. 2a&c, these results are consistent with Wang (2017) because the vertical integration in the KE calculation and the non-linear relationship between KE and the eddy winds sharpens the changes in KE versus the signatures in temperature observations. Murphy et al (1995) also found a slowly propagating westward wave in their global dust storm simulation and suggested that the westward wave signals polar warming.…”
Section: Evolution Of Globally Averaged Eddy Kinetic Energysupporting
confidence: 78%
“…Thus, the 8 < P ≤ 60 sol eddies are closely related to mature, large dust storms and not all dust storm sequences. Wang (2017) found that westward traveling waves are among the signatures of major dust storms on Mars. Those traveling waves are characterized by wave periods longer than about 15 sols and are included in the 8 < P ≤ 60 sol eddies shown in Fig.…”
Section: Evolution Of Globally Averaged Eddy Kinetic Energymentioning
confidence: 99%
“…Nevertheless, these steady‐state model results do provide some general climatological insights into why some tidal components are likely candidates to explain the MO and MRO longitudinal structures during certain seasons, and why other tides are not. Throughout both MO and MRO aerobraking missions, phases of k s =1 and k s =2 are characterized by zonal migrations with periods between 15 and 45 sols; clean eastward migrations for MO but both eastward and westward migrations occur for MRO. A rudimentary analysis demonstrates that these migrations plausibly arise from modulations of D0, S0, and DE1 by slow waves in the lower atmosphere that have been reported in the literature (Banfield et al, ; L. Wang, ; Wilson et al, ). At low to middle latitudes k s =3 and k s =4 density variations (±15%) occur at about half the amplitudes of k s =1 and k s =2 (±30%). MO and MRO amplitudes and phases at latitudes between 20° and 45° latitude are in good agreement and are attributable to DE2 and DE3, respectively.…”
Section: Discussionmentioning
confidence: 70%
“…Moreover, they are characterized by significant hemispheric asymmetries and interannual variability in terms of wave periods and amplitudes. Dust storm onset during NH winter can alter the slow wave behavior, in particular, trigger the switchover from eastward to westward traveling slow waves (Banfield et al, ; H. Wang, ; Wilson et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…To understand the results in section 3.1, this study examines the dominant wave mode of 1.2 < P ≤ 20 sols eastward traveling waves on both σ levels. Although westward traveling waves are present during major dust storms, they are mostly filtered out in this study due to their long wave periods (Banfield et al, ; Wang, ). Figures and show the results derived from the T and V fields, respectively.…”
Section: Resultsmentioning
confidence: 99%